Who pays the price for development? Evidence from selected videos. Issue 2 (3rd April 2019) - Kamruzzaman, Palash
Abstract : Broadly speaking, development apparently intends to improve the livelihoods of the poor and marginalised people. However, this paper assesses whether this is always the case. Could development come at a price? If yes, who pays the price? This paper investigates this further based on cinematic representations of three non-fiction documentary videos: Drowned Out (2002), Dying for a Bargain (2013), and Black Gold (2006). Interpretive analyses of the storylines of these videos suggest that despite the promises of making a positive change for the better, development, often in practice, might affect the poorest through unfair wage and calls for 'sacrifices' for a so-called larger common good.